Altered phospholipid and high-energy phosphate metabolism in the basal ganglia and thalamus of severe obsessive compulsive patients with treatment resistance: A phosphorus 31 nuclear magnetic resonance spectroscopy study. (30th January 2021) - Hatchondo, Laura; Vallée, Alexandre; Vallée, Rodolphe; Jaafari, Nemat; Maillochaud, Sylvie; Naudin, Mathieu; Vallée, Jean-Noël; Guillevin, Rémy; Guillevin, Carole
Highlights: First study of 31 P-MRS in OCD at 3 tesla. Significantly increased concentrations of PC, PDE, PME, GPC, PME/PCr, PDE/PCr in OCD patients compared to controls in the striatum and thalamus. Significantly decreased concentrations of PCr and tATP in OCD patients compared to controls in the striatum. Modifications of the membrane and energy metabolism in the basal ganglia of severe OCD patients. ABSTRACT: Introduction: Cerebral metabolism in obsessive-compulsive-disorder(OCD) has been the subject of numerous studies using proton magnetic resonance spectroscopy(MRS). Despite heterogeneous results, some studies have unraveled membrane turnover and energy metabolism abnormalities in different brain regions, suggesting that alterations in these processes may contribute to the pathophysiology. So far, no authors have explored phospholipids and high-energy phosphate metabolism using 31 P-MRS, which allows in vivo quantification of phosphorus metabolites that are considered to be related to membrane turnover and energy metabolism. Materials and Methods: The aim of our study was to describe and compare brain metabolic changes using 31 P-MRS in the striatum and the thalamus, between 23 severe OCD patients and 22 healthy controls. All subject underwent a clinical examination and a same 31 P-MRS protocol. Results: Significantly, increased concentrations of PC, PDE, PME, GPC, PME/PCr, PDE/PCr were found in patients compared to controls in the striatum and the thalamus. PCr and tATP were decreased in the striatum. Finally, significant correlations were found in the striatum and the thalamus between illness duration and some specific measured parameters. Conclusion: Our results showed significant modifications of the membrane and energy metabolism in the basal ganglia of severe OCD patients and suggests a link between energetic buffer and serotonin metabolism disorder.